The influence of Performance Expectations, Business Expectations, and Facilitating Conditions on Interest in Using the QRIS System - Himayor Zidan; Zakky Fahma Auliya (Dinamis : Journal of Islamic Management and Bussiness, 2023)
The purpose of this research is to analyze the effect of performance expectations, business expectations, and facilitating conditions on interest in using the QRIS system. The population in this study were students studying at three major universities in Solo Raya, namely students at UIN Raden Mas Said Surakarta, Muhamadiyah University Surakarta and Sebelas Maret University Surakarta. The sample in this study is prospective QRIS users who will use QRIS in the payment transaction method. There were 114 respondents used in this study. The data were analyzed using the IBM SPSS Statistik software version 26. This research method is a quantitative research method. The data analysis method used is multiple linear regression analysis. The results of the study show that: (1) Performance Expectations have no effect on Interest in using the QRIS system. (2) Business Expectations have a significant effect on Interest in Using the QRIS system. (3) facilitating conditions have a significant effect on Interest in Using the QRIS system.